Determination of Relationship of Maxillary Occlusal Plane with Ala-Tragus Line: A Customised Approach in Aryan and Mongolian Ethnicity. - Mehta, Pawan; Chhetri, Shanti (Journal of Nobel Medical College, 2019)
Background: Determining occlusal plane is challenging and difficult aspect during complete removable partial denture prosthesis rehabilitation. Numerous soft tissue landmarks like commissures of the mouth by Gillis in 1933, parotid papilla by P. F. Foley and G. H. Latta in 1985, height of the retromolar pad, the lateral borders of the tongue etc. had been proposed to assist clinician for determining the occlusal plane. No universally accepted reliable anatomical measurement has been proposed to assist in determining of occlusion plane for different ethnic groups in context to Nepal.Material & Methods: This cross-sectional study was conducted in the 60 dentate subjects visiting Nobel Medical College, Nepal, from February 2019 to July 2019. A customized occlusal plane relator was used to evaluate relative parallelism between occlusal plane and alatragal line with respect to different borders of tragus. All the data were collected and statistically analyzed.Results: Maxillary occlusal plane was found to be parallel with the line drawn from ala of the nose to the middle of tragus in 66.66%, followed by inferior border of tragus in 18.33% with the least parallelism in superior border of tragus 15%. Relationship of maxillary occlusal plane with alatragal line was not statistically significant among Aryans and Mongolian ethnicityConclusion: This study showed line joining ala of the nose and middle border of tragus is parallel to maxillary occlusal plane. And no difference was found for Aryan & Mongolian ethnicity in relation to alatragal line and maxillary occlusal plane.